Yield Yield loss and economic threshold estimates for pod borer (Helicoverpa armigera) in late maturing pigeonpea (Cajanus cajan) - BANDI, SANJAY M; REVANASIDDA,; NAIK, SATHEESH; SINGH, A K; KATIYAR, P K (The Indian Journal of Agricultural Sciences, 2024)
Pod borer [Helicoverpa armigera (Hubner)] is a major biotic constraint to global pigeonpea production. The farmers largely apply synthetic insecticides to control this pest in pigeonpea. The study was conducted to quantify yield losses and estimate economic thresholds for H. armigera. The late maturing cultivar, IPA-203 was infested with different larval densities to determine the insect density-yield loss relationships. The yield response was variable and grain yield declined with increasing larval density from 1–5/plant. Yield loss of 4.56 kg/ha was evident for each unit increase in larval population. Economic threshold estimates indicated that the control measures for pod borer in IPA 203 cultivar should be initiated at an insect density of ≈1 larva/2 plants or at 3% pod damage to avoid the economic crop losses. The damage potential and economic threshold estimates are prerequisite for integrated pest management and reducing production costs (Alves et al. 2017). Present results indicated that relatively low infestations of H. armigera can cause significant yield reduction in pigeonpea hence intensive monitoring and timely control measures are necessary. Based on present economic threshold estimates, the farmers could decide the timing and kind of control measures to be initiated against pod borer in late pigeonpea cultivars to avert the economic losses.